Harga Pokok Produksi Budidaya Ikan Gurame Skala Rumah Tangga Di Desa Tenggur, Rejotangan, Tulungagung - Ayuningsih, Eka; Syafii, Syafii; Hidayati, Kusni (Equity: Jurnal Akuntansi, 2024)
Gurame farming business is one of the economic activities that are in the interest of the community. This study aims to determine and analyze the Cost of Goods Produced in household-scale gurame farming businesses. The object of his research is a household-scale gurame farming in Giring, Tenggur Village, Rejotangan District, Tulungagung Regency. The results of this study show the determination of Cost of Goods Produced, comparation of cost of goods produced with receipts from production results and determination of the target market for household-scale gurame farming business.